Rapid tree carbon stock recovery in managed Amazonian forests - Rutishauser, Ervan; Hérault, Bruno; Baraloto, Christopher; Blanc, Lilian; Descroix, Laurent; Sotta, Eleneide Doff; Ferreira, Joice; Kanashiro, Milton; Mazzei, Lucas; d’Oliveira, Marcus V.N.; de Oliveira, Luis C.; Peña-Claros, Marielos; et al. (Current biology, 2015)
While around 20% of the Amazonian forest has been cleared for pastures and agriculture, one fourth of the remaining forest is dedicated to wood production [1]. Most of these production forests have been or will be selectively harvested for commercial timber, but recent studies show that even soon after logging, harvested stands retain much of their tree-biomass carbon and biodiversity [2,3]. Comparing species richness of various animal taxa among logged and unlogged forests across the tropics, Burivalova et al.[4] found that despite some variability among taxa, biodiversity loss was generally explained by logging intensity (the number of trees extracted). Here, we use a network of 79 permanent sample plots (376 ha total) located at 10 sites across the Amazon Basin [5] to assess the main drivers of time-to-recovery of post-logging tree carbon (Table S1). Recovery time is of direct relevance to policies governing management practices (i.e., allowable volumes cut and cutting cycle lengths), and indirectly to forest-based climate change mitigation interventions. Rutishauser et al. assess the main drivers underlying the time taken for a logged forest to recover its carbon capture and find that forests with reduced impact logging recover more quickly.